Learning to Teach, Imaginatively: Supporting the Development of New Teachers Through Cognitive Tools - Egan, Kieran; Bullock, Shawn; Chodakowski, Anne (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
We propose that teacher candidates need to have extended experiences with learning to teach imaginatively, which is to say that teacher candidates need to have experiences that enable them to consider new possibilities in education. We first attend to the general theoretical framework offered by imaginative education before moving on to consider the implications of imaginative education for teacher education programs. We conclude with some provocations to the field that we hope will be of use for those who might wish to join us in considering how we might teach teachers to teach in imaginative ways — a complex sentence with an even more complicated set of implications.